(untitled) (Journal of Medicine, 2024)
Background: Non-alcoholic fatty liver disease (NAFLD) encompasses the simple steatosis to more progressive steatosis with associated hepatitis, fibrosis and cirrhosis. Though accurate diagnosis of simple fatty liver (SFL) and non-alcoholic steatohepatitis (NASH) can be made by liver biopsy, it is not feasible to be done in all NAFLD patients. Relationship of C-reactive protein (CRP) with NAFLD was well documented in many populations, but comprehensive data is lacking in Bangladeshi people. Method: This case-control study was conducted at the Medicine, Gastroenterology and Hepatology departments in Dhaka Medical College Hospital from March to August 2018 involving 30 patients with NAFLD as case and apparently healthy 30 individuals as control. Abdominal ultrasound to detect fatty liver and serum CRP level estimation by nephelometry were performed for each subject to compare between two groups. Result: Majority of the NAFLD cases and healthy controls were female (70% and 60% respectively). Mean age was 47.53±9.69 year in NAFLD group and 46.03±8.44 year in healthy controls. NAFLD cases had significantly higher mean serum CRP concentration (6.27±1.80) mg/dl than that of healthy controls (3.94±2.16) mg/dl (p<0.001). Overweight/obesity and dyslipidaemia were found as significant risk factors for NAFLD compared to the healthy control group (p<0.05). Conclusion: NAFLD cases had significantly higher CRP than the control group. But, to find out the association of increasing CRP level with the severity of NAFLD and to establish it as a diagnostic tool, further extensive studies are recommended. J MEDICINE 2024; 25: 5-10